Pharmacological activities and medicinal uses of berberine: A review - Shams, Gamal; Abd Allah, Somia; Ezzat, Raghda (Journal of Advanced Veterinary Research, 2024)
Berberine (BBR) is an isoquinoline derivative alkaloid that has been identified from a variety of plant species including Cortex phellodendron (Huang bai), Hydrastis canadensis (goldenseal), and Rhizoma coptidis (Huanglian). A growing body of research has demonstrated that this chemical has a wide range of biological functions, including antioxidant and anti-inflammatory, anticancer, and anti-hyperglycemic properties. BBR has been proven in studies to reduce the production of inflammatory mediators such as TNF-, IL-1, IL-6, and IL-8. Furthermore, BBR appears to boost the cellular antioxidant defense mechanism by raising the activity of CAT, SOD, and GPx while reducing OS variables such as protein carbonyl (PC) content, MDA, and NO levels. This review threw light on the pharmacological activities and medicinal uses of BBR.